The Effect Of Phet Simulation On The Discovery Learning Model On Critical Thinking Skills Of Sma Students On Straight Motion Materials - Dermawan Saputra; Sunaryono, Sunaryono (INOVASIA, 2022)
Critical thinking is a competency that must be trained in students because this ability is needed in today's life. Discovery learning models can help students eliminate their doubts about a concept because it leads to a final and definite truth. This study aims to determine the effect of PhET simulation on the Discovery learning model on students' critical thinking skills. The research was conducted at SMA Negeri 1 Sape, Jalan Pelabuhan Sape, Bima, West Nusa Tenggara. The data collection technique in this study used a test instrument to measure students' thinking skills. Utilizing tests at the beginning of learning (pre-test) and tests at the end of learning (post-test), the results of the pre-test and post-test are the data to determine students' critical thinking skills. The data analysis used is parametric analysis. The results of this study show a significant effect between the PhET simulation and the Discovery learning model on students' critical thinking skills in the form of an increase in post-test scores that occur in the experimental class using PhET-based learning.